Implementation of value stream mapping techniques in improving the performance of service industry - Suarno, Agha Khilfi; Norazlianie, Sazali; Afdhal, Junaidi (Springer Nature, 2025)
Efficiently managing operations is essential in the current competitive service business to stay relevant in the market and meet consumer expectations. This study explores the application of value stream mapping (VSM) as a strategic tool to improve service performance by identifying and eliminating operations that do not contribute value. We illustrate the pragmatic implementation of VSM in a particular service company by employing a case study methodology, gathering data through direct observation, interviews, and analysis of process flowcharts. The results demonstrate substantial enhancements following the implementation of VSM. These include a noteworthy 28.7% reduction in cycle time, a 27.1% decrease in takt time, a decrease in workforce size from 28 to 23 individuals, an improvement in value-added time from 19.5 h to 15.7 h, and an increase in process cycle efficiency from 32.55% to 44.31%. The findings emphasize the transformative influence of VSM on the efficiency of processes, allocation of resources, and happiness of customers. This paper presents empirical evidence that supports the applicability of VSM (Value Stream Mapping) in service sectors. It highlights the importance of VSM in fostering continuous improvement and operational excellence. It provides practical and useful information for businesses aiming to improve efficiency and provide outstanding service experiences.